Sabretoothed carnivores and the killing of large prey. - Ki Andersson (Public Library of Science (PLoS), 2011)
Sabre-like canines clearly have the potential to inflict grievous wounds leading to massive blood loss and rapid death. Hypotheses concerning sabretooth killing modes include attack to soft parts such as the belly or throat, where biting deep is essential to generate strikes reaching major blood vessels. Sabretoothed carnivorans are widely interpreted as hunters of larger and more powerful prey than that of their present-day nonsabretoothed relatives. However, the precise functional advantage of the sabretooth bite, particularly in relation to prey size, is unknown. Here, we present a new point-to-point bite model and show that, for sabretooths, depth of the killing bite decreases dramatically with increasing prey size. The extended gape of sabretooths only results in considerable increase in bite depth when biting into prey with a radius of less than ∼10 cm. For sabretooths, this size-reversed functional advantage suggests predation on species within a similar size range to those attacked by present-day carnivorans, rather than "megaherbivores" as previously believed. The development of the sabretooth condition appears to represent a shift in function and killing behaviour, rather than one in predator-prey relations. Furthermore, our results demonstrate how sabretoothed carnivorans are likely to have evolved along a functionally continuous trajectory: beginning as an extension of a jaw-powered killing bite, as adopted by present-day pantherine cats, followed by neck-powered biting and thereafter shifting to neck-powered shear-biting. We anticipate this new insight to be a starting point for detailed study of the evolution of pathways that encompass extreme specialisation, for example, understanding how neck-powered biting shifts into shear-biting and its significance for predator-prey interactions. We also expect that our model for point-to-point biting and bite depth estimations will yield new insights into the behaviours of a broad range of extinct predators including therocephalians (gorgonopsian + cynodont, sabretoothed mammal-like reptiles), sauropterygians (marine reptiles) and theropod dinosaurs.